Family law : a very short introduction - Herring, Jonathan (Oxford, United Kingdom : Oxford University Press, 2014)
"What is a family? What makes someone a parent? What rights should c hildren have? [This book] gives the reader insight not only into what t he law is, but why it is the way it is. It examines how laws have had t o respond to social changes in family life, from rapidly rising divorce rates to surrogate mothers, and gives insight into family courts, whic h are required to deal with the chaos of family life and often struggle to keep up-to-date with social and scientific changes. It also looks t o the future: what will families look like in the years ahead? What new dilemmas will the courts face?" --Provided by publisher.
Marriage, civil partnership, and cohabitation -- Domestic violence - - Divorce -- Parents -- Children's rights -- Child abuse -- Alimony and financial orders -- Where next for family law?
Includes bibliographical references (p. 113-116) and index.
Keywords: Domestic relations